PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN MATEMATIKA SDN CIODENG CIGUDEG BOGOR - Siti Rahmawati; Taufiq Nur Azis; Nailil Muna Shalihah (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2025)
This study aims to investigate the impact of learning motivation on the academic outcomes of fifth-grade students in mathematics at SDN Ciodeng, Cigudeg District, Bogor Regency. This study is motivated by the low learning outcomes of students who have not yet met the Minimum Completion Criteria (KKM) and the lack of motivation for learning. This is a quantitative study using a survey method with regression techniques. The sample in this study consisted of 31 students from class V.A. The instruments used in this study were a questionnaire to measure learning motivation and a test to measure students' learning outcomes in mathematics. Data analysis was conducted through validity, reliability, normality, linearity tests, and simple regression analysis using SPSS 22.0 software. The results of the study indicate that the students' learning motivation is in the high category, with an average score of 102.77, while the average learning outcome in mathematics is 82.58. The simple regression test results show a significance value of 0.000 < 0.05, indicating a positive and significant effect of learning motivation on mathematics learning outcomes. Therefore, the higher the students' learning motivation, the higher their mathematics learning outcomes.